Hellebrigenina, um bufodienolídeo com potencial ação compatível de inibidor catalítico da topoisomerase II - Soares, Bruno Marques (2013)
Bufodienolides are cardioactive steroids of 24 carbons, originally isolated from a frog’s skin extract of the family Bufonidae used in Chinese medicine. Bufodienolides shows many biological activities, including anticancer activities. Related to antitumor activity, the bufodienolídeos has been shown to inhibit the growth of several human cancer cell lines by inducing apoptosis and cell cycle arrest. This study evaluated the potential cytotoxicity and genotoxicity of six bufodienolides, in six human tumor cell lines, three normal murine lineages and PBMC (peripheral blood mononuclear cells). All six bufodienolides were cytotoxic to all cell lines and tumor PBMC with IC50 values ranging from 0.002 to 3.17 µM. Bufodienolides showed no cytotoxicity for normal murine strains. Thus, the compound hellebrigenin was chosen to determine the action mechanism involved, a sequence of in vitro experiments were performed using HL-60 leukemia cell line. Cells were treated at different concentrations of hellebrigenin (0.03, 0.06 and 0.12 µM) for 24 hours. Cell viability (viable cell number and membrane integrity) HL-60 assessed by flow cytometry showed that the number of cells decreased from the lower concentration (0.03 µM) tested and the percentage of cells with reduced membrane integrity from 0.06 µM concentration. Morphological analysis by flow cytometry revealed increased apoptotic cells starting at concentrations of 0.06 µM. The analysis of nuclear content, showed an increase in DNA fragmentation indicative of sub-G1 apoptosis and accumulation of cells in G2 / M phase from the concentrations of 0.03 and 0.06 µM, respectively. Other tests by flow cytometry revealed that there was an externalization of phosphatidylserine, mitochondrial depolarization, activation of caspase 8 and initiating subsequent activation of effector caspases 3 and 7. These data indicate a cytotoxic mechanism induced by over an apoptotic pathway. Hellebrigenin was not able to cause DNA damage in HL-60 and PBMC nor the emergence of chromosomal aberrations in PBMC. Through the studies of molecular docking was possible to predict the connection between hellebrigenina and human topoisomeraseIIα, showing a result that is compatible with a possible inhibition of this enzyme. Overall, the results indicate the potential cytotoxicity of hellebrigenin.